Improvement of mechanical and thermal properties of high energy electron beam irradiated HDPE/hydroxyapatite nano-composite. (January 2017) - Mohammadi, M.; Ziaie, F.; Majdabadi, A.; Akhavan, A.; Shafaei, M.
Abstract: In this research work, the nano-composites of high density polyethylene/hydroxyapatite samples were manufactured via two methods: In the first method, the granules of high density polyethylene and nano-structure hydroxyapatite were processed in an internal mixer to prepare the nano-composite samples with a different weight percentage of the reinforcement phase. As for the second one, high density polyethylene was prepared in nano-powder form in boiling xylene. During this procedure, the hydroxyapatite nano-powder was added with different weight percentages to the solvent to obtain the nano-composite. In both of the procedures, the used hydroxyapatite nano-powder was synthesized via hydrolysis methods. The samples were irradiated under 10 MeV electron beam in 70–200 kGy of doses. Mechanical, thermal and morphological properties of the samples were investigated and compared. The results demonstrate that the nano-composites which we have prepared using nano-polyethylene, show better mechanical and thermal properties than the composites prepared from normal polyethylene granules, due to the better dispersion of nano-particles in the polymer matrix. Highlights: HDPE/HAP nano-composite sample were prepared in nano-powder form. All the samples were made in thin sheet form using warm press system. The samples were subjected to irradiation under 10 MeV EB in different doses. Mechanical and thermal properties of the samples were compared. Mechanical and thermal parameters are strongly dependent on HAP dispersion.